Anaphylaxis in the Pediatric Emergency Department of a central hospital - Coelho, Cristina (2024)
Anaphylaxis is a potentially life-threatening medical emergency. Early diagnosis and treatment are crucial. In children, the diagnosis is complicated by some unique features of the pediatric population. Food is the most common etiology in pediatric patients. The aim of this study was to characterize the episodes of anaphylaxis identified in the Pediatric Emergency Department (ED) of a central hospital between 2012 and 2021 according to the 2014 EAACI guidelines. Seventy-eight anaphylaxis episodes were included, 44 of which were first episodes. Children’s median age was 9.5 years (range 6 months-17 years) and 62.8% were male. A history of atopy was present in 52.6% of cases and asthma and/or allergic rhinitis in 50.9%. The most common trigger was food (74.4%) and the most common food was milk (27.6%). Mucocutaneous manifestations occurred in 94.9%, respiratory manifestations in 80.8%, gastrointestinal manifestations in 38.5%, and cardiovascular manifestations in 21.8%. Epinephrine treatment was administered in 83.3% of episodes. Patients with an epinephrine autoinjector (EAI) used it in 52.9% of episodes. The median (range) monitoring time was 13 (3-26) hours. At discharge, EAI was prescribed in 84.1% of first episodes, and 95.5% were referred for specialty consultation. As reported in the literature, food etiology prevailed in the described anaphylaxis cases. Epinephrine was the first-line treatment in most cases. EAI was used in approximately half of patients. Despite growing awareness, it is essential to alert patients and health professionals to the importance of epinephrine in the management of these cases.